Digital Transformation as a Catalyst for the Success of Health-Related SMEs Going International in Indonesia: A SEM-PLS Analysis Model - Achmad Zani Pitoyo; Sudarmiatin Sudarmiatin; Heri Pratikto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Health-related SMEs in Indonesia have significant opportunities to enter international markets, but many businesses still face limitations in digital capabilities, innovation, and readiness for external markets. This study aims to examine the influence of digital transformation on the success of health-related SMEs in going international, both directly and through business innovation as a mediator. The study employs a quantitative approach using a cross-sectional survey design involving 200 owners or key managers of SMEs in East Java, selected via purposive sampling. Data were analysed using Structural Equation Modelling-Partial Least Squares (SEM-PLS). The results indicate that digital transformation has a positive influence on business innovation and the success of going international. Business innovation also has a positive effect on internationalisation success and mediates the relationship between digital transformation and external market success. These findings confirm that digitalisation should not merely be understood as an operational tool, but as a strategic capability that must be integrated with product, process, marketing, and business model innovation. The research implications emphasise the importance of strengthening digital capabilities and business innovation to enhance the global competitiveness of Indonesian health-related SMEs.